Begonia medicinalis: a review of Phytochemistry and Pharmacology - Velincia Tanriono, Levana; Hayati, Farida; Zubair, Muhammad Sulaiman (Universitas Islam Indonesia, 2024)
Background: Begonia medicinalis, often referred to as benalu batu, is a plant belonging to the Begoniaceae family. It is renowned for its wide range of pharmacological activities and its extensive application in the treatment of many diseases. Saponins, tannins, flavonoids, phenolics, steroids, alkaloids, and triterpenoids are some of the chemical compounds in this plant responsible for its pharmacological activity.Objective: The aim of this review is to provide information about the phytochemical and pharmacological properties of B. medicinalis.Method: This narrative review was performed by conducting literature searches on various relevant reputable online databases, and there were 17 articles that discussed the phytochemistry and pharmacology activity of B. medicinalis. Results: People have long used B. medicinalis as a test treatment for a variety of diseases. Flavanols, 2-O-β-glucopyranosyl cucurbitan D, β-sitosterol-3-O-β-D-glucopyranoside, and 9(11)α,16(17)α-dioxirane-20,25-dihydroxy-β-sitosterol-3-O-β-glucopyranoside are among the compounds found in the plant. Studies have demonstrated the immunomodulatory, anticancer, antiviral, and antioxidant activity of this plant. In vitro toxicity tests revealed that this plant is toxic and has anticancer potential. The in vivo toxicity test revealed that this plant has mild toxicity.Conclusion: This study suggests that B. medicinalis has strong potential for future development into herbal medicine.Keywords: Begonia medicinalis; Begonia sp.; pharmacological; phytochemical